Disrupção destruidora : as práticas comunicacionais do aplicativo UBER em Porto Alegre - Guimarães, Tiago da Costa (2018)
This essay is a study of the impacts of disruptive organizations, taking as case study the Uber Technologies, defined for this research as a disruptive company, choosed for being one of the most prominent and controversial within the present-day capitalism’s new shape of own business. Uber Technologies communication practices are evidenced and discussed as an innovative organization, whose discourse is constructed according to their stakeholders. Therefore, its tactics include charm the printed media using the innovative speech and the quality improvement of the public transportation service, which can be reached through competition dynamics. This way, it is assumed that this model follower companies are ruled for an unbridled quest for innovation, causing market ruptures and pre-made social models, even analyzing, thereupon, the social impacts provoked by Uber Technologies. The research has a bibliographic and documentary character. The bibliographic character based on the disruption and creative destruction, based on the works of Christensen (2001), Schumpeter (1961) and Harvey (2011). The similarities of virtuality and ubiquity with the concepts of place and non-place, are presented from the works of Àuge (1994), Lévi (1996,1999), Santaella (2007) and Santos (2008). We also reviewed different perspectives of the organizational studies, drawing on the works of Baldissera (2010), Chanlat (2010), Freitas (1999), Hall (2006), Han (2017), Kunsch (2008), Mumby (2013), Schiraro (2004) and Srour (2012). The analysis of the Uber news published in the newspapers Zero Hora and Correio do Povo in the period from november 2015 to april 2018 showed at first the disruptive impact of the organization and, later, its trajectory and regulation. In turn, the Uber advertising campaign sought to humanize the relations between passengers/customers and drivers, representing situations of lightness and good acquaintanceship provided by the application. The presence of Uber Technologies is recent in the world, and with its maturation, new guidelines can become relevant in the eyes of the media organizations, acquiring more space in the social agenda.